2021
DOI: 10.1111/jgh.15435
|View full text |Cite
|
Sign up to set email alerts
|

Early course of newly diagnosed moderate‐to‐severe ulcerative colitis in Korea: Results from a hospital‐based inception cohort study (MOSAIK)

Abstract: Background and Aim:No inception cohort study has ever evaluated the early course of moderate-to-severe ulcerative colitis (UC) within 1 year of diagnosis in the non-Caucasian population. We aimed to investigate the early clinical course of moderateto-severe UC patients in terms of remission, relapse, UC-related hospitalizations, colectomy, mortality, and overall use of medications. Methods: In the MOSAIK inception cohort, which is an ongoing multicenter, prospective, hospital-based, observational cohort, 354 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…Adoption of Western guidelines is difficult, because IBD treatment in Korea requires special clinical consideration of regional differences in infectious diseases [8][9][10]. However, well-designed, epidemiological cohort studies have demonstrated several characteristics of Korean patients with IBD that may be useful when seeking to understand the condition [7][8][9]11,12]. The results of these studies provide valuable fundamental data allowing improvements in IBD care using both the Internet and IBD center-oriented management [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Adoption of Western guidelines is difficult, because IBD treatment in Korea requires special clinical consideration of regional differences in infectious diseases [8][9][10]. However, well-designed, epidemiological cohort studies have demonstrated several characteristics of Korean patients with IBD that may be useful when seeking to understand the condition [7][8][9]11,12]. The results of these studies provide valuable fundamental data allowing improvements in IBD care using both the Internet and IBD center-oriented management [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…In this MOSAIK cohort, 276 people remained in the first-year analysis, and follow-up is planned for the next 5 years, so the future trend seems favorable. 5 Meanwhile, the results of the MOSAIK cohort were better than those of other cohort studies, and it is noteworthy whether these differences will continue in future HRQL. On the other hand, due to the limitations of the method for assess HRQL used in this study, evaluation through innovative technology such as mobile applications were not used.…”
mentioning
confidence: 92%
“…As a result, the study successfully started with 368 patients and published 1-year follow-up data in 2021. 5 One-year follow-up of 276 patients was reported. Specifically, the MOSAIK study collected the Inflammatory Bowel Disease Questionnaire (IBDQ) and the 12-Item Short Form Health Survey (SF-12) at every follow-up from baseline.…”
mentioning
confidence: 99%